Student's perception and satisfaction towards mentor's role and responsibilities among UPSR students in Kuala Selangor - Norziani Zubir (Institute of Education, International Islamic University Malaysia, 2011)
The purpose of this study was to explore the extent of the importance of the roles of mentor as perceived by students in Kuala Selangor. It is also examined the satisfaction of the students towards mentors' role and responsibilities. It attempts to improve mentoring program at primary school especially for UPSR students. To achieve this purpose, a sample of 122 students in Kuala Selangor primary school who had gone through the mentoring program was selected. This study employed a survey instrument adapted from studies done by Yeoh Siok Tee (1997). One hundred and fifty sets of questionnaire were distributed to students in Kuala Selangor. The respondents returned 122 completed questionnaires. The data collected was tested using SPSS version 12.5. The major findings of this study revealed that mentoring program very important among UPSR students. The level of students' satisfaction can be rated as satisfied towards mentors' role and responsibilities. It is recommended that the relationship between mentor and mentee be considered when assessing the quality of mentors' role and responsibilities.